Trials of Dual Antiplatelet Therapy After Percutaneous Coronary Intervention Lack Strategies to Ensure Appropriate Gastroprotection. (13th April 2021) - Kurlander, Jacob E.; Barnes, Geoffrey D.; Sukul, Devraj; Helminski, Danielle; Kokaly, Alex N.; Platt, Kevin; Gurm, Hitinder; Saini, Sameer D.
Abstract : INTRODUCTION: Gastrointestinal bleeding is a morbid complication of dual antiplatelet therapy (DAPT). We evaluated the extent to which contemporary trials of DAPT included steps to ensure appropriate use of proton pump inhibitor (PPI) gastroprotection and reported rates of PPI use. METHODS: A methodological review of randomized trials comparing varying durations of DAPT after percutaneous coronary intervention. RESULTS: Among 21 trials, none incorporated protocol procedures or guidance for prescribing PPIs. Five reported rates of PPI use (range 25.6–69.1%). DISCUSSION: PPI gastroprotection is overlooked in major trials of DAPT. Appropriate use of PPI gastroprotection represents an important opportunity to improve patient safety.